Al-Tarikh Salasilah Negeri Kedah: A Malay World Literary Heritage: (Al-Tarikh Salasilah Negeri Kedah: Sebuah Warisan Dunia Persuratan Melayu) (Malay Literature, 2019)
The state of Kedah Darul Aman has a manuscript writing tradition that is directly related to the existence of its institution of Malay royalty and nobles. Manuscripts from Kedah possess unique features that are consistent with the cultural life of its society and system of monarchy. However, the history of manuscript writing that originated in Kedah remains incomplete due to the lack of information sources and material collection. This problem affects the preservation of Kedah cultural heritage, including the effort to put forward great works that originated in the state. This article will discuss an important manuscript that originated in Kedah and is currently in the safekeeping of Dewan Bahasa dan Pustaka, Kuala Lumpur. The manuscript is entitled Al-Tarikh Salasilah Negeri Kedah (History and Genealogy of the State of Kedah) and should appropriately be presented as a Malay world literary heritage that came into existence from the penmanship of a writer in Kedah in the early 20th century.Keywords: great works, world heritage, manuscript, sultanate, nationhood